A switched-capacitor power converter with unequal duty cycle for ripple reduction and efficiency improvement. (October 2020) - Wu, Yulun; Mustafa, Yerzhan; Lu, Yan; Ruderman, Alex; Martins, Rui P.
Abstract: This work applies unequal duty cycle to switched-capacitor (SC) dc-dc converters to improve its output ripple as well as the power conversion efficiency. By adjusting the duty cycle, the capacitor charge and discharge states are reasonably balanced. Therefore, we effectively reduce the output ripple and the charge redistribution loss, improving the efficiency. A SC converter verifies this scheme with voltage conversion ratios (VCRs) of 1/4 and 1/3, in a 65 ​nm CMOS low-power process. Operating with a switching frequency of 33 ​MHz, an input voltage of 2.4 ​V, an output range of 0.5–25 ​mA, and a VCR of 1/4, the peak efficiency increases by 1.0% and the output ripple drops by 43.6%, when compared with the equal duty cycle mode. With the input voltage equal to 1.8 ​V and the VCR ​= ​1/3, the peak efficiency increases by 0.7% and the output ripple reduces by 48.0%, compared to the equal duty cycle mode.